Determination of geometric characteristics of explosive eruptions on agricultural lands using remote methods - Horelyk, S.; Nechausov, A.; Yankin, O. (Land Management, Cadastre and Land Monitoring, 2023)
The armed aggression of the Russian Federation against Ukraine led to significant damage to the fertile soil layer in the temporarily occupied territories. Damage assessment for agricultural lands damaged by ravines requires determination of their geometric characteristics. There are two groups of methods for finding the area and volume of pits. The first group is contact geodetic research, which allows you to accurately determine the parameters of craters, but it is impossible to apply them due to the explosiveness of the territory and the large number of damaged areas. Other methods are related to the determination of geometric characteristics based on the data of remote sensing of the Earth (RS). They make it possible to quickly identify the location of explosive holes, but in wartime they are not fully available. Therefore, the complex use of remote sensing data and contact research will allow to quickly and safely determine the location and geometric characteristics of explosive craters. The purpose of the study is to develop a methodology for determining the geometric characteristics of explosive craters due to the complex use of contact and remote geodetic data in the conditions of military operations. The main tasks of the research: analysis of existing methods for determining the geometric characteristics of explosive craters; determination of the relationship between the force of the explosion and the geometric characteristics of the eruption; development of a methodology for determining damage to the fertile layer of agricultural lands from military operations using Geoinformation technologies (GIS technologies); practical implementation of the developed methodology on the example of a test plot of agricultural land. The developed technique consists in the use of geo-information technologies and data of RS to determine the location and area of explosive craters. Based on the existing statistical relationships between the TNT equivalent of the explosion and the geometric characteristics, new functions of the relationship between the radius of the rupture and the volume, depth, and TNT equivalent of the explosion were obtained. Cartographic models of the distribution of craters by volume, the density of explosive craters and their distribution by radius were built in the ArcGIS geoinformation software. The constructed geomodels made it possible to assess the degree of damage to agricultural soils and to determine the most explosive areas. Based on the obtained data, it was established that there is no correlation between the density of the holes and their radius in the presence of holes larger than 25 m. Assessment of damage to agricultural land as a result of military operations in Ukraine requires the use of images from UAVs and satellites with ultra-high spatial resolution. In the future, it is necessary to check the adequacy of the developed methodology by field geodetic methods.